Determination of phytochemical characteristics of the extract of Zea mays with Saccharomyces boulardii - Erecevit, Pinar; Kirbag, Sevda; Yilmaz, Okkes (Springer, 2013)
Fatty acid, vitamin, phytosterol, flavonoid, and resveratrol contents and antimicrobial activities of Zea mays L. (corn) extracts treated with Saccharomyces boulardii were determined and compared. The total fatty acid, vitamin, and phytosterol contents in corn extract were at certain levels. It was detected that total fatty acid levels and vitamin contents of corn extracts prepared with Saccharomyces boulardii increased; however, flavonoid contents decreased at different rates. In addition to this, it was observed that naringin, resveratrol, and myricetin flavonoids were present in the extracts that contained S. boulardii. In the study, it was noticed that Z. mays L. (corn) had antioxidant and antimicrobial activities at different rates. It was observed that S. boulardii developing in extracts obtained from plants affected bioactive compounds at different rates.
Keywords: Saccharomyces boulardii; Zea mays L. (corn); fatty acids; phytosterol; vitamins